Can we improve partner notification rates through expedited partner therapy in the UK? Findings from an exploratory trial of Accelerated Partner Therapy (APT). Issue 1 (27th July 2011) - Estcourt, Claudia; Sutcliffe, Lorna; Cassell, Jackie; Mercer, Catherine H; Copas, Andrew; James, Laura; Low, Nicola; Horner, Patrick; Clarke, Michael; Symonds, Merle; Roberts, Tracy; Tsourapas, Angelos; et al.
Abstract : Objectives: To develop two new models of expedited partner therapy for the UK, and evaluate them for feasibility, acceptability and preliminary outcome estimates to inform the design of a randomised controlled trial (RCT). Methods: Two models of expedited partner therapy (APTHotline and APTPharmacy), known as 'Accelerated Partner Therapy' (APT) were developed. A non-randomised comparative study was conducted of the two APT models and routine partner notification (PN), in which the index patient chose the PN option for his/her partner(s) in two contrasting clinics. Results: The proportion of contactable partners treated when routine PN was chosen was 42/117 (36%) and was significantly higher if either APT option was chosen: APTHotline 80/135 (59%), p=0.003; APTPharmacy 29/44 (66%) p=0.001. However, partner treatment was often achieved through other routes. Although 40–60% of partners in APT groups returned urine samples for sexually transmitted infection (STI) testing, almost none accessed HIV and syphilis testing. APT options appear to facilitate faster treatment of sex partners than routine PN. Preferences and recruitment rates varied between sites, related to staff satisfaction with existing routine PN; approach to consent; and possibly, characteristics of local populations. Conclusions: Both methods of APT were feasible and acceptable to many patients and led to higher rates of partner treatment than routine PN. Preferences and recruitment rates varied greatly between settings, suggesting that organisational and cultural factors may have an important impact on the feasibility of an RCT and on outcomes. Mindful of these factors, it is proposed that APT should now be evaluated in a cluster RCT.